Development and implementation of a quality control program for the Varian TrueBeam® linear accelerator - Sousa, Eva Maria da Silva (2022)
Quality assurance (QA) aims to ensure that a product or service being evaluated has always the desired quality. In the radiotherapy field , QA is a pivotal process for the health or even the patient's life at risk. A QA protocol in this field mainly applies to the dose delivered to a target volume, the minimum dose delivered to normal tissue , safety, exposure of medical personnel present, and proper monitoring of the patient before, during and after treatment . To ensure good treatment, a protocol of routine and systematic actions is applied , the result compared to quality and repeatability goals, and , in case of significant deviations, restoration and return to normality actions are carried out. This regulatory process is called quality control (QC), and is the main focus of this work. The Julio Teixeira , S.A. clinic recently acquired a Varian TrueBeam linear accelerator for which the development of a QA protocol is needed. This work focuses on carrying out quality tests for linear accelerators, previously outlined by the European Commission . Additionally, tests outlined in the TECDOC 1583 reports from the International Atomic Energy Agency and 119 from the American Association of Physicists in Medicine were presented in order to ensure the proper functioning of Varian TrueBeam linear accelerator. Multi- institutional tests were also carried out. The quality control protocol for the Varian TrueBeam linear accelerator was developed and all the tests were successfully performed . As such , the Varian TrueBeam linear accelerator is ready for treatment.